EFFECT OF 30° HEAD-UP POSITION ON INTRACRANIAL PRESSURE CHANGE IN PATIENTS WITH HEAD INJURY IN SURGICAL WARD OF GENERAL HOSPITAL OF Dr. R. SOEDARSONO PASURUAN - Sumirah Budi Pertami; Sulastyawati Sulastyawati; Puthut Anami (Public Health of Indonesia)
Background: Head-injured patients have traditionally been maintained in the head-up position to ameliorate the effects of increased intracranial pressure (ICP). However, it has been reported that the 15 degrees head-up position may improve cerebral perfusion pressure (CPP) and outcome. We sought to determine the impact of 30 and 15 degrees on intracranial pressure change.